Impact of climate change on yield and farmers’ production behaviour in northern maize Belt, Nigeria - Ndawayo, Adamu Buba (2017)
Climate change caused challenge for all sectors of economy, particularly rainfed agriculture, studies show that overall crop productivity in sub-Saharan Africa is likely to decline due to weather change effects. This has consequence for world food security in developing countries including Nigeria, with subsequent effect on yield harvest, reduction of farm income and total inefficiency in crop production. Maize production in Nigeria as in other developing countries is extremely vulnerable to changes in weather conditions (temperature, carbon-dioxide and rainfall). This problem can results to famine and poverty amongst farmers and low income earners, most countries were net importer of food. The main goal is to estimate the impact of climate change on maize yield and farmers’ production behaviour in northern maize belt, Nigeria. With specific objectives of analysing and forecasting maize yield, evaluating and analysing farmers’ perceptions on climate change with appropriate adjustment measures and determine production behaviour. Study method applied interdisciplinary approach by using decision support system for agrotechnology transfer crop simulation model (DSSAT – CSM) in forecasting maize yields until (2039) with secondary data of (temperature, rainfall and solar radiation) recorded between (1992 – 2015) period from institute of agriculture research Zaria (IAR) and managements data from national agriculture extension research and liaison services (NAERLS) Zaria; Analytical hierarchy process (AHP) criteria were developed from (2014) household survey of farmers’ perception on climate change with 400 respondents, using cluster sampling technique. Stochastic frontier analysis model (SFAM) was used to estimate risk, inefficiency and technical efficiency of respondents, other statistical tool were used to compare variables. DSSAT – CSM forecasting, indicate average yields reduction by 8.5% until 2039. The AHP results indicate mitigation as best criteria. SFAM mean estimation shows the presence of both risk and inefficiency in the production, Lambda_λ is largely caused by inefficiency, estimated Gamma_γ = 54.5%. The production technical efficiency score = 87.5%. There exist significant difference between different vegetation zones and rainfall regimes technical efficiency. The independent-sample t-test for extension services and farmers’ association, perception and farming status shows significant difference, cross tabulation and chi square of perception and gender indicate significant level. Policy makers were recommended to proper funding of research institution for staff training and modern facilities, peasant farmers’ should have access to credit schemes, extension services, and timely information’s on climate change. Crop production provides employment to rural populations and raw-materials to urban industries in Nigeria. Findings are significant to both farmers and government to prepare for future climate impact on maize yield and would serve as frame work to policy makers on self-sufficiency maize production.